2002
DOI: 10.1021/ma011991j
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Ring-Opening Polymerization of Trimethylsiloxy-Substituted 1-Oxa-2,5-disilacyclopentanes:  Synthesis of Trimethylsiloxy-Substituted Poly[1-oxa-2,5-disila-1,5-pentanylene]s

Abstract: 2,5,5-Trimethyl-2-trimethylsiloxy-1-oxa-2,5-disilacyclopentane (I), cis-and trans-2,5-dimethyl-2,5-bis(trimethylsiloxy)-1-oxa-2,5-disilacyclopentane (II), and 2-methyl-2,5,5-tris(trimethylsiloxy)-1-oxa-2,5-disilacyclopentane (III) have been prepared from 1,3,5,7-tetramethylcyclotetrasiloxane (D4 H ) and vinylpentamethyldisiloxane, vinylmethylbis(trimethylsiloxy)silane, and vinyltris(trimethylsiloxy)-silane, respectively, by a two-step synthetic process. I, II, and III undergo anionic ring-opening polymerizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The anionic ring-opening polymerisation (ROP) of strained 1-oxa-2,5-disilacyclopentanes has been reported. 29 Molecular dynamics simulations have been used to study the structure of liquid PDMS and the results were found to be in good agreement with data obtained using wide-angle X-ray scattering. 30 The chain dynamics of PDMS in its inclusion compound with γ-cyclodextrin were studied using fast-MAS solid-state NMR spectroscopy.…”
Section: Group 14 Element-containing Polymers: Polysiloxanes (Silicon...supporting
confidence: 65%
See 2 more Smart Citations
“…The anionic ring-opening polymerisation (ROP) of strained 1-oxa-2,5-disilacyclopentanes has been reported. 29 Molecular dynamics simulations have been used to study the structure of liquid PDMS and the results were found to be in good agreement with data obtained using wide-angle X-ray scattering. 30 The chain dynamics of PDMS in its inclusion compound with γ-cyclodextrin were studied using fast-MAS solid-state NMR spectroscopy.…”
Section: Group 14 Element-containing Polymers: Polysiloxanes (Silicon...supporting
confidence: 65%
“…The synthesis and fluorescent properties of a pyrene end-functionalised PDMS have been investigated. 25 The mechanism of the cationic polymerisation of 2,2-diphenyl-4,4,6,6-tetramethylcyclotrisiloxane initiated by triflic acid has been studied using 29 Si NMR at the pentad level and statistical methods. 26 The results suggested that monomer addition giving symmetrical siloxane -OSiMe 2 -OSiPh 2 -OSiMe 2 -(68%) and unsymmetrical siloxane -OSiMe 2 -OSiMe 2 -OSiPh 2 -(32%) units dominated the chain growth process.…”
Section: Group 14 Element-containing Polymers: Polysiloxanes (Silicon...mentioning
confidence: 99%
See 1 more Smart Citation
“…Poly(carbosiloxane)s are polymers that contain both siloxane (SiOSi) and carbosilane (SiC) bonds in the polymer backbone 1. Copoly(carbosiloxane)s are most frequently prepared by the ring opening of cyclosilaalkylenesiloxanes or by metal‐catalyzed addition reactions such as the Pt‐catalyzed hydrosilylation copolymerization of tetramethyldisiloxane and diallyldimethylsilane 1–5. Copoly(silarylene siloxane)s are usually prepared by condensation reactions between a 1,4‐bis(hydroxyldialkylsilyl)benzene and a suitable comonomer such as α,ω‐bis(chloro)oligodimethylsiloxane or α,ω‐bis(amino)oligodimethylsiloxane 6–10.…”
Section: Introductionmentioning
confidence: 99%
“…They might be regarded as silicon analogs of crown ethers, since they form different-sized rings of alternating silicon and oxygen atoms, with various side chains (R = hydrogen atoms, alkyl, or vinyl groups) attached to silicon. 12 These compounds are characterized by flexibility, high strength of Si-O bonds, and high reactivity under specified conditions in miscellaneous organic reactions, i.e., hydrolysis, 13 halogenation, 14 dehydrogenative couplings, 15,16 silylative coupling, 17,18 alkylative cleavage, 19 Piers-Rubinsztajn reaction, 20 ring-opening polymerizations, 21,22 and hydrosilylation. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] 8-Membered compounds such as DH 4 , because of the possible modification of peripheral Si-H groups by a hydrosilylation reaction, have opened access to several functional materials.…”
Section: Introductionmentioning
confidence: 99%